Responsible Corporate Officer Doctrineas a New Idea in The National Criminal Code (KUHP) on Criminal Liability in Corporations - Ilahi, M. Ridho; Rahma, Meida Adita; Lutfiya Nitha, Fitha Ayun (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2024)
AbstractThe National Criminal Code, which was recently passed, contains several new provisions that have not been regulated in the Criminal Code used to date, while the provisions in question are corporate criminal liability. The focus of this research is criminal liability imposed on management (executive/superior) in a corporation in terms of article 48 letters d and e. In order to analyze the laws and regulations which are used as the main basis of the research, the researcher uses a normative method by using several international and national sources in the form of theories and explanations that are relevant to the article which is the focus of the discussion of this research. Based on this research, it can be understood that one of the concepts of criminal responsibility in the corporate sector regulated in the National Criminal Code is the responsible corporate officer (RCO) doctrine. However, this model of criminal responsibility is not fully adhered to in the National Criminal Code. Even the RCO concept will look vague if you don't review articles 46 and 49 of the National Criminal Code. In addition, criminal liability based on (RCO) needs to consider AD/ART in corporations considering that this type of accountability model is closely related to sectors within corporations.Abstrak          KUHP Nasional yang belum lama ini disahkan memuat beberapa ketentuan baru yang belum diatur pada KUHP yang digunakan sampai saat ini. Adapun ketentuan yang dimaksud adalah pertanggungjawaban pidana korporasi. Adapun fokus pada penelitian ini adalah pertanggungjawaban pidana yang dibebankan pada pengurus (eksekutif/atasan) dalam korporasi yang ditinjau dari pasal 48 huruf d dan e. Guna menganalisis aturan perundang-undangan yang dijadikan landasan utama penelitian, peneliti menggunakan metode normatif dengan menggunakan beberapa sumber baik internasional maupun nasional berupa teori dan penjelasan yang relevan dengan pasal yang menjadi fokus pembahasan penelitian ini. Berdasarkan penelitian ini dapat dipahami  Salah satu konsep pertanggungjawaban pidana dalam sektor korporasi yang diatur pada KUHP Nasional adalah doktrin responsible corporate officer (RCO). Namun model pertanggungjawaban pidana tersebut tidak dianut sepenuhnya pada KUHP Nasional bahkan konsep RCO akan terlihat samar jika tidak meninjau pada pasal 46 dan 49 KUHP Nasional. Selain itu pertanggungjawaban pidana berdasarkan (RCO) perlu mempertimbangkan AD/ART dalam korporasi mengingat model pertanggungjawaban jenis ini erat kaitannya dengan sektoral dalam korporasi.